2010
DOI: 10.1086/651672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of USA300 Strain Type of Methicillin-Resistant Staphylococcus aureus among Patients with Nasal Colonization Identified with Active Surveillance

Abstract: The proportion of MRSA nasally colonized patients with USA300 strains significantly increased during the study, and risks included African American race. Strain type had no significant effect on the proportion of patients who developed infection, and risk factors for infection were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
(23 reference statements)
2
18
1
Order By: Relevance
“…The reason for this difference appears to be that invasive MRSA rates among black children aged ≤2 years increased, while rates among older black persons decreased. One retrospective hospital cohort study identified African American race and younger age as risk factors for USA300 MRSA nasal colonization, the most prevalent strain type of CA MRSA [18]. A recent analysis suggests that racial differences in invasive CA MRSA rates are due to socioeconomic factors, which may include decreased availability and affordability of medical care, increased crowding, and higher poverty rates [19].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference appears to be that invasive MRSA rates among black children aged ≤2 years increased, while rates among older black persons decreased. One retrospective hospital cohort study identified African American race and younger age as risk factors for USA300 MRSA nasal colonization, the most prevalent strain type of CA MRSA [18]. A recent analysis suggests that racial differences in invasive CA MRSA rates are due to socioeconomic factors, which may include decreased availability and affordability of medical care, increased crowding, and higher poverty rates [19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found USA300 MRSA to be more common than other strains in the nares and at all body sites of control subjects. A previous study examining MRSA nasal colonization among hospitalized patients found that 24% of MRSA nasal isolates were USA300 and that the proportion of USA300 increased from 2005 to 2007 (29).…”
Section: Discussionmentioning
confidence: 98%
“…The USA300 strain type of MRSA is capable of spreading rapidly 13 and has been associated with African-American race. 14 Another explanation is differential access to health care in minority races 15 and therefore delays in presentation. A previous study examining health care disparities documented longer LOS among minority children with appendicitis.…”
Section: Discussionmentioning
confidence: 99%